The FMEA Traditional Modifications (FMEA Improvement) in IT Risk Assessment: The FMEA Traditional Modifications - Nina Fadilah Najwa; Apol Pribadi Subriadi; Okfalisa; Eki Saputra; Muhammad Ariful Furqon (International ABEC, 2021)
Failure mode effect and analysis (FMEA) was an essential technique in risk management. Various studies have revealed the shortcomings of FMEA, one of them is about subjectivity and the consistency of the results issues. This research contributed to the FMEA improvement as the improvement Model to minimize traditional FMEA consistency issues. Based on previous research, the present study will discuss in more detail the FMEA improvement method. The research questions formulated for this research are: (1) How was the use of the FMEA improvement model in the case study; and (2) What were the implications of the FMEA improvement model. The FMEA Improvement Model consisted of four main stages, namely: (1) the determination of risk assessment requirements; (2) risk identification; (3) risk analysis; and (4) evaluation and the recommendation control documentation. From the results of risk level categorization, one risk was at the highest level. This risk was classified as severe because it often happens almost every day. Two risks were at the medium to the high level, three risks were at the medium level, 13 risks were at the low to medium level, and 18 risks were low. Therefore, this paper's contribution was to guide researchers or IT experts to apply the FMEA improvement.